Pengaruh Kualitas Pelayanan, Customer Experience, dan Kepercayaan terhadap Kepuasan Pelanggan pada CV Bharata Mas Teknik (Lembaga Pengembangan Kinerja Dosen, 2026)
Customer satisfaction is a crucial factor in determining the success of service companies in retaining their customers. Service quality, customer experience, and trust are key elements that influence the level of customer satisfaction. These three factors play a significant role in establishing long-term relationships between companies and their customers. High service quality enhances customers’ positive perceptions, pleasant experiences strengthen loyalty, and trust encourages customers to continue using the services offered. This study aims to examine the effects of service quality, customer experience, and trust on customer satisfaction at CV Bharata Mas Teknik in Denpasar. The population of this study consists of all customers of CV Bharata Mas Teknik, with a sample of 126 respondents selected using purposive sampling. The analytical tool employed to test the hypotheses is multiple linear regression analysis using SPSS version 25. The results indicate that service quality, customer experience, and trust each have a positive and significant effect on customer satisfaction at CV Bharata Mas Teknik. This finding implies that improvements in service quality, customer experience, and trust contribute to higher levels of customer satisfaction. Based on the results, CV Bharata Mas Teknik is advised to continuously enhance service quality, customer experience, and trust to support sustainable improvements in customer satisfaction.